1996
DOI: 10.1139/v96-257
|View full text |Cite
|
Sign up to set email alerts
|

Parallel vs. perpendicular alkyne coordination in binuclear complexes. The first examples of reactivity differences in isomers differing in their alkyne coordination modes

Abstract: Abstract:The reaction of [Ir,(CO),(dppm),] (dppm = Ph,PCH,PPh,) with dimethyl acetylenedicarboxylate (DMAD) first yields [ I~~( c o )~(~, -~' :~~-D M A D ) (~~~~)~](2) in which the alkyne is bound parallel to the metal-metal axis and the diphosphines are bound in a trans arrangement at both metals. This metastable isomer slowly rearranges to the stable form, [ I~~( C O ) , (~, -~~:~~-D M A D ) (~~~~)~](3), in which the alkyne is now bound perpendicular to the metals and the diphosphines are bent back in a cis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…These assignments have been confirmed by 13 C− 1 H NMR correlation experiments. The observed pattern suggests that the bonding of the allyl ligand approaches the σ, π-coordination mode, as is found for [RhM(η 3 -C 3 H 5 )(CO) 3 (dppm) 2 ] (M = Os, Ru). 6b,43b Although the chemical shifts are also consistent with an η 1 -allyl group, which normally gives rise to signals at δ 2.0−3.5 for the methylene protons and δ 3.5−5.5 for the olefinic hydrogens, coupling observed between the iridium-bound phosphines and all five hydrogens on the allyl ligand is consistent with η 3 -coordination. In addition, the high-field protons (H a H b ) would be expected to be equivalent in an η 1 -allyl.…”
Section: Results and Compound Characterizationsupporting
confidence: 53%
See 3 more Smart Citations
“…These assignments have been confirmed by 13 C− 1 H NMR correlation experiments. The observed pattern suggests that the bonding of the allyl ligand approaches the σ, π-coordination mode, as is found for [RhM(η 3 -C 3 H 5 )(CO) 3 (dppm) 2 ] (M = Os, Ru). 6b,43b Although the chemical shifts are also consistent with an η 1 -allyl group, which normally gives rise to signals at δ 2.0−3.5 for the methylene protons and δ 3.5−5.5 for the olefinic hydrogens, coupling observed between the iridium-bound phosphines and all five hydrogens on the allyl ligand is consistent with η 3 -coordination. In addition, the high-field protons (H a H b ) would be expected to be equivalent in an η 1 -allyl.…”
Section: Results and Compound Characterizationsupporting
confidence: 53%
“…Alkynyl groups have also been implicated as intermediates in the transformation of 1-alkynes to vinylidenes . Certainly, in binuclear late-metal complexes we have shown that this transformation is extremely facile and have proposed that it is facilitated by the μ-η 1 :η 2 -alkynyl binding mode, in which migration of the hydride ligand from an intermediate such as C to the alkynyl β-carbon occurs readily, as diagrammed in eq 1. 6h, Intermediate C can be considered as containing a metal-substituted alkyne moiety (RC⋮CM), which is π-bound to the second metal, with the process shown in eq 1 being analogous to migratory insertion involving mutually cis hydride and alkyne ligands. We sought to extend this analogy to carbanionic ligands in efforts to induce migration of an alkyl or related group from one metal to the adjacent β-carbon of an μ-η 1 :η 2 -alkynyl group.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…These spectroscopic data do not distinguish between a bridging phenylacetylene ( C ) or a phenylvinylidene ligand ( D ), and location of the phenylacetylene-derived carbons in the 13 C{ 1 H} NMR spectrum in order to differentiate between the two bonding modes was unsuccessful. Coordination of terminal alkynes in a bridging mode or in a rearranged vinylidene mode is common in binuclear complexes. 6b,,, In both structures C and D , the phenyl group derived from phenylacetylene is shown to be directed away from the molybdenum center in order to minimize steric interactions with the molybdenum-bound ligands. The possibility of having the alkyne η 2 -bound to molybdenum is ruled out, based on the already crowded environment at this metal.…”
Section: Results and Compound Characterizationmentioning
confidence: 99%